Long-term outcome of the IMZ implant system: a retrospective clinical study with a follow-up between 23 and 34 years - Christoph Mautsch; Stefan Wolfart; Walter Mautsch; Anne Barbara Rittich (SpringerOpen, 2022)
Abstract Purpose To evaluate the radiographic and peri-implant outcomes of intramobile cylinder implants (IMZs) and the feasibility of long-term follow-up studies after nearly 30 years. Methods Of the 94 patients treated with IMZ implants between 1981 and 1995, 39 patients were successfully contacted (contact group, CG), of which 15 patients with a total of 32 implants agreed to participate in the present follow-up study (clinical evaluation group, CEG). The overall implant survival rate was calculated. Information on implant status and oral and general health data was collected. Marginal bone level was evaluated and then compared to the patients' baseline data. Possible risk factors for peri-implantitis were also identified. Results In total, 16 implants in seven patients were lost, amounting to an overall survival rate of 79.5% after 30 years with a mean follow-up time of 24 ± 10 years (CG). Eight patients were treated with bar-retained mandibular overdentures and seven patients had fixed partial dentures. After a mean observation time of 29 ± 3 years, the surviving implants showed a peri-implantitis rate of 9.4% with a mean marginal bone loss of 2.5 ± 1.8 mm (CEG). No significant correlation between peri-implantitis and possible risk factors could be found. Conclusions Long-term follow-up studies with acceptable response rates after nearly 30 years are not feasible. Contact was only possible with 41% of the patients. This contact group showed a high implant survival rate. Due to the retrospective study design, additional risk factors could not be considered in a conclusive analysis. Graphical Abstract